ANALYSIS OF THE NEED FOR HYPERMEDIA E-MODULES IN DIFFERENTIATED SOCIAL STUDIES LEARNING: A CASE STUDY IN ELEMENTARY SCHOOL - Yuyun Dwi Haryanti; Mochamad Guntur; Sinta Maria Dewi; Syarif Sumantri; Mahpudin Mahpudin; Okeu Santika; Lutvi Nurhadiansyah (Program Studi PGSD Universitas Flores, 2025)
Differentiated social studies learning is the right solution according to the learning needs of students, but there are still limited digital teaching modules that can meet the diverse needs of students in heterogeneous classrooms. This study aims to analyze the need for the development of hypermedia-based e-modules in Social Sciences (IPS) learning that applies a differentiated approach at the elementary school level. The method used is qualitative descriptive with a case study approach in several elementary schools in Indonesia. Data was collected through questionnaires, teacher and student interviews, and classroom observations to identify gaps between current learning conditions and actual needs in the field. The results of the analysis showed that teachers experienced obstacles in delivering social studies materials effectively to students with different abilities and learning styles. In addition, the available learning media has not been able to stimulate students' creative thinking skills optimally. Therefore, it is necessary to develop hypermedia e-modules that are interactive, adaptive, and able to support differentiation strategies and encourage students' creative thinking skills. These findings provide an empirical basis for designing digital learning modules that are contextual and responsive to the needs of the 21st century in primary schools.